Air Quality Status in Wuhan City during and One Year after the COVID-19 Lockdown - Crystal Jane Ethan; Kingsley Katleho Mokoena; Yan Yu (Aerosol and Air Quality Research)
Abstract Anthropogenic activities have been established to have severe adverse effects on air quality. Consequently, the nature of daily events, directly and indirectly, influences the nature of air pollution observed. This study focused on describing air quality one year after the Coronavirus (COVID-19) pandemic lockdown (since anthropogenic activities had resumed back to normal) in Wuhan. Using the independent t-test, the means of air quality index (AQI) and individual air pollutants concentration during the lockdown were compared with the means after the lockdown. Cohen’s d was estimated to quantify the standardized mean difference observed. Based on the average AQI, the air quality in Wuhan during and after the lockdown was rated “good”; and ranged between 59.7 and 99.8. Indicators of traffic pollution, particularly NO2, were significantly higher after the lockdown; noting a 162% increment in concentration. A 36% increase was also noted for ozone immediately after the lockdown; while a 33% increase was noted for SO2 roughly eight months post lockdown. At different periods post lockdown, particulate matter pollution varied, with some time-spans observing lower concentrations and others higher concentrations than the lockdown. A trade-off effect between PM2.5 and O3 was also noted during and after the lockdown. One year post the lockdown, air quality in Wuhan has observed some drastic changes. Hence, there is a need for more studies to identify other specific and peculiar sources of emissions in the city. Relevant findings should be employed in supporting the implementation of stringent emission control.